Assessing new developments in the pre-market regulatory process of medical devices in the People's Republic of China. (September 2014) - Zhang, Shixuan; Kriza, Christine; Kolominsky-Rabas, Peter L
Abstract : The objective of this paper is to provide a systematic overview of the Chinese medical device registration processes, identify challenges and suggest how these can be addressed. In addition, the paper will outline the impact of new policies and regulations since the restructuring of the China FDA. A systematic review was performed for journal articles between the year of 2009 and 2013 in the following databases: PubMed, ScienceDirect and Zhongguozhiwang. The review has identified 184 papers which were potentially relevant. Seventeen articles were included in the review, which highlights the challenges and opportunities related to the medical device registration process. In order to understand the actual impact of the regulation environment and its policies including the lack of regulatory guidance regular assessment updates are crucial. The results of this paper are aimed at informing regulatory bodies, health policy decision makers, national and international Health Technology Assessment networks as well as medical devices manufacturers.